Cascade cycling of nicotinamide cofactor in a dual enzyme microsystem. Issue 18 (5th February 2020) - Lv, Rui; Lin, Sen; Sun, Shiyong; He, Huichao; Zheng, Fei; Tan, Daoyong; Ma, Biaobiao; He, Meng
Abstract : A functionalized microsystem capable of sustainable cascade cycling of NAD + /NADH via chemical signaling between spatially confined dual-enzyme and active membranes. Abstract : Encapsulation of two enzymes, alcohol dehydrogenase (ADH) and glucose oxidase (GOx), within peroxidase-like tourmaline microparticle (TM)-based colloidosomes was used to construct a functionalized microsystem capable of sustainable cascade cycling of nicotinamide cofactor (NAD + /NADH) via chemical signaling between spatially confined dual-enzyme and active membranes.